1999
DOI: 10.1046/j.1523-1747.1999.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

UVB Activates ERK1/2 and p38 Signaling Pathways via Reactive Oxygen Species in Cultured Keratinocytes

Abstract: We have previously shown that hydrogen peroxide is an important mediator of ultraviolet B induced phosphorylation of the epidermal growth factor receptor in human keratinocytes. Here we demonstrate that physiologic doses of ultraviolet B and hydrogen peroxide stimulate activation of two related but distinct mitogen-activated protein kinase pathways: extracellular regulated kinase 1 and 2 (ERK1/2), as well as p38, the mammalian homolog of HOG1 in yeast which is a major kinase for a recently identified stress-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
175
1
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 232 publications
(189 citation statements)
references
References 44 publications
12
175
1
1
Order By: Relevance
“…Peus et al reported that inhibition of ERK by PD98059 resulted in increased UVB-induced cell death [9]. ERK, however, was not significantly phosphorylated by UVB in SVHK…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Peus et al reported that inhibition of ERK by PD98059 resulted in increased UVB-induced cell death [9]. ERK, however, was not significantly phosphorylated by UVB in SVHK…”
Section: Discussionmentioning
confidence: 99%
“…The In many cells including keratinocytes, UVB irradiation-induced apoptosis depends on p38 [9,17,31]. Still UVB-induced activation of ERK and JNK has been reported in normal human keratinocytes and in HaCaT cells [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phosphorylation of the MAPK proteins, namely, ERK1/2, JNK and p38, has been shown to be mediated through UVB-induced oxidative stress [17,32,33]. We examined UVB-induced phosphorylation of MAPK proteins using densitometric analysis of western blots and expressed the data in terms of the ratio of the levels of phosphorylated MAPK to the levels of the unphosphorylated form.…”
Section: Uvb Exposure-induces Higher Photo-oxidative Damage Of Lipidsmentioning
confidence: 99%